Application Of Seft (Spiritual Emotional Freedom Technique) To Reduce Anxiety In Hypertension Patients Through The Application Of Comfort Kolcaba Theory At Simpang Nangka Community Health Center, Rejang Lebong Regency - Ratih, Rina Puspita; Handayani, Tita Septi (Journal of Nursing, 2025)
According to WHO (2023), the global prevalence of hypertension is 22% of the total world population. According to the Ministry of Health (2023), the highest incidence of hypertension in Indonesia was found in North Sulawesi Province at 13.21%, East Kalimantan at 10.57%, North Kalimantan at 10.46%, DKI Jakarta at 10.17%, and Southeast Sulawesi at 10.17% from 300,000 selected and visited households. The purpose of this study is to understand and apply SEFT (Spiritual Emotional Freedom Technique) to reduce anxiety in patients with hypertension through the application of Kolcaba’s Comfort Theory at Simpang Nangka Health Center, Rejang Lebong Regency. The research method used in this study is a case study. The subject of this research was used to explore the application of SEFT (Spiritual Emotional Freedom Technique) to reduce anxiety in patients with hypertension through the application of Kolcaba’s Comfort Theory at Simpang Nangka Health Center, Rejang Lebong Regency.The results of the study on Client 1 and Client 2 showed that in Case 1 and Case 2, anxiety problems could be resolved. It can therefore be concluded that the application of SEFT (Spiritual Emotional Freedom Technique) is effective in reducing anxiety in patients with hypertension through the application of Kolcaba’s Comfort Theory It is expected that the Health Center will support the use of safe non-pharmacological therapies, such as warm red ginger compresses, in managing pain in pregnant women by providing adequate facilities and infrastructure.